Mechanisms of formation and correction corporate culture - Melnikov A. M. (Economic science today: theory and practice, 2017)
This article includes exploration of the main mechanisms of formation and correction corporate culture. There is also provided characteristics of these mechanisms.
Keywords: взаимодействие; корпоративная культура; механизмы формирования; воздействие; влияние; корректировка; Influence; teamwork; corporate culture; Impact; adjustment; mechanisms of formation